2017
DOI: 10.3389/fpls.2017.01227
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilizer Deep Placement for Increased Grain Yield and Nitrogen Recovery Efficiency in Rice Grown in Subtropical China

Abstract: Field plot experiments were conducted over 3 years (from April 2014 to November 2016) in a double-rice (Oryza sativa L.) cropping system in subtropical China to evaluate the effects of N fertilizer placement on grain yield and N recovery efficiency (NRE). Different N application methods included: no N application (CK); N broadcast application (NBP); N and NPK deep placement (NDP and NPKDP, respectively). Results showed that grain yield and apparent NRE significantly increased for NDP and NPKDP as compared to N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 32 publications
3
27
0
5
Order By: Relevance
“…Thus, in this study, gaseous N losses by NH 3 volatilization may have reflected the actual losses more closely since the fertilizer (SRF or urea) was applied at a depth of 10 cm and covered with soil. Other studies indicated that the best measure to obtain higher N use efficiency and reduce N losses is by placing fertilizer at 15-20 cm depth, especially when using slow-release urea in the growing season of maize [13,45,48]. Moreover, it is well known that another important factor governing the NH 3 volatilization is ammonical N concentration [49,50].…”
Section: Fate Of 15 N-labeled Urea Affected By N Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in this study, gaseous N losses by NH 3 volatilization may have reflected the actual losses more closely since the fertilizer (SRF or urea) was applied at a depth of 10 cm and covered with soil. Other studies indicated that the best measure to obtain higher N use efficiency and reduce N losses is by placing fertilizer at 15-20 cm depth, especially when using slow-release urea in the growing season of maize [13,45,48]. Moreover, it is well known that another important factor governing the NH 3 volatilization is ammonical N concentration [49,50].…”
Section: Fate Of 15 N-labeled Urea Affected By N Managementmentioning
confidence: 99%
“…Lower nitrogen recovery efficiency (NRE), and different environmental consequences, such as soil acidification, N leaching, ammonia volatilization, and groundwater contamination etc. are becoming ever more serious [11][12][13]. This phenomenon is particularly of concern in intensive cropping systems [2,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous field studies showed that deep fertilizer placement, compared to broadcast application, increased yields, improved NUE, and decreased N runoff (Mengel et al 1982;Kelley and Sweeney 2007;Xia et al 2016;Zhu et al 2019). Regarding N 2 O emissions, however, results are rather contradicting: while deep N fertilizer placement effectively lowered N 2 O emissions in rice paddies (Gaihre et al 2015;Wu et al 2017) and field experiments comparing conservation tillage methods (Liu et al 2006;Nash et al 2012), other studies (e.g. Cai et al 2002;Drury et al 2006;Chu et al 2007) found that N 2 O emissions were higher from deeper N placement compared to shallow N placement.…”
Section: Introductionmentioning
confidence: 98%
“…O N do fertilizante (N-fertilizante) depois de aplicado no solo pode ser volatilizado (N-NH3), nitrificação, desnitrificado (N-NxO e N-N2), lixiviado e imobilizado pela comunidade microbiana. A perda por volatilização de N-NH3 varia entre 30% e 80% (Adjetey et al, 1999;Prasertsak et al, 2002;Rees et al, 1997;Tewari et al, 2007;Wu et al, 2017;Yao et al, 2017) e acontece pela aplicação de ureia (N-amídico) na superfície do solo. Na zona de dissolução desse fertilizante o pH pode ser igual a 10 (Nômmik e Nilsson, 1963), situação em que o amônio (N-NH4 + ) é transformado em amônia (N-NH3) -gás volátil.…”
Section: Introductionunclassified
“…Diversas pesquisas foram realizadas com o objetivo de avaliar a aplicação de ureia em profundidade para reduzir a perda por volatilização (Adjetey et al, 1999;Prasertsak et al, 2002;Rees et al, 1997;Tewari et al, 2007;Wu et al, 2017;Yao et al, 2017). Os resultados indicaram que o aproveitamento de N e a produtividade aumentaram, no entanto, não se pode descartar que esta vantagem auferida se deva, em parte, à diminuição da imobilização do N. Na presente pesquisa, foi utilizado o nitrato de amônio (NH4NO3) em diferentes profundidades, a fim de desconsiderar o benefício proporcionado pela não volatilização de N aplicado na superfície.…”
Section: Introductionunclassified